Auditing Revocable Privacy-Preserving Access Control for EHRs in Clouds. (10th August 2017) - Liu, Weiran; Liu, Xiao; Liu, Jianwei; Wu, Qianhong
Abstract: Electronic Health Record (EHR) systems bring an abundance of convenience for telediagnosis, medical data sharing and management. A main obstacle for wide adoption of EHR systems is due to the privacy concerns of patients. In this work, we propose a role-based access control (RBAC) scheme for EHR systems to secure private EHRs. In our RBAC, there are two main types of roles, namely independent patients and hierarchically organized medical staffs. A patient is identified by his/her identity, and a medical staff is recognized by his/her role in the medical institute. A user can comprehend an EHR only if he/she satisfies the access policy associated with this EHR, which implies a fine-grained access control. A public auditor is employed to verify whether the EHR is correctly encapsulated with the specified access policy, which provides an a priori approach to find fraudulent EHRs and reduce potential medical disputes. Moreover, our RBAC enforces a forward revocation mechanism. A revoked user cannot access the future EHRs even if his/her previous role satisfies the access policy. These security properties are formally proven under well-established assumptions. Theoretical and experimental analyses show the efficiency of our RBAC in terms of communication and computation.